Parametric strategic management: genesis & pracsis - A. Yu. Obydenov (Стратегические решения и риск-менеджмент)
The author’s concept of parametric strategic management approach is considered in accordance with generally accepted strategic management conceptions. Simultaneously the article makes an attempt to substantiate application of qualitative comparative analysis as a relevant method of empirical verification and to construct one-dimensional model of employee’s labor participation as the demonstration of practical application of the author’s concept